Suspension high velocity oxy-fuel spraying of a rutile TiO 2 feedstock: microstructure, phase evolution and photocatalytic behaviour - Bai, M.; Khammas, R.; Guan, L.; Murray, J.W.; Hussain, T. (Elsevier, 2017)
Nano-structured TiO2 coatings were produced by suspension high velocity oxy fuel (SHVOF) thermal spraying using water-based suspensions containing 30 wt% of submicron rutile powders (~180 nm). By changing the flame heat powers from 40 kW to 101 kW, TiO2 coatings were obtained with distinctive microstructures, phases and photocatalytic behaviour. Spraying with low power (40 kW) resulted in a more porous microstructure with the presence of un-melted nano-particles and a lower content of the anatase phase; meanwhile, high powers (72/101 kW) resulted in denser coatings and rougher surfaces with distinctive humps but not necessarily with a higher content of anatase. Linear sweep voltammetry (LSV) was used to evaluate the photocatalytic performance. Surprisingly, coatings with the lowest anatase content (~20%) using 40 kW showed the best photocatalytic behaviour with the highest photo-conversion efficiency. It was suggested that this was partially owing to the increased specific surface area of the un-melted nano-particles. More importantly, the structural arrangement of the similarly sized TiO2 nano-crystallites between rutile and antase phases also created catalytic “hot spots” at the rutile−anatase interface and greatly improved the photo-activity.